Analisis Tingkat Kebisingan Di Kawasan Kampus Fakultas Kedokteran Universitas Riau - Saputra, Eko Hendi; Sasmita, Aryo; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Noise is one of environmental problem that should be given an attention, because noise with high intensity can cause negative impacts to human’s health, comfort and psychology. Noise in school or campus area can interfere with process of teachingand learning. The purpose of this research is to analyze noise level at Faculty of Medicine UR and provide solutions to control the noise in that area. The procedure of noise measurement was done according to the regulation of Minister of Environment No. 48 1996 attachment II about Measurement Method. The measurement and evaluation of environment noise level used Sound Level Meter in13 spots for 2 days (weekend and weekday). The result shows, maximum noise occurred on Sunday at spot number 1 with 89.1 dB noise level. Primary source of the noise came from traffic activity. This is shown by the result of noise measurement of89.1 from 6664 vehicles that passed by spot number 1 on Sunday and 83.3 dB from 6264 vehicles passed by spot number 1 on Monday. This research recommends noisecontrol solutions by substitution control, technical control and administrative control.Keywords: Noise, Sound Level Meter, LSM